Masticatory performance and masticatory behavior in individuals with eating disorders: a pilot study - Kumar, Abhishek; Munirji, Linda; Langlet, Billy; Bostanci, Nagihan; Grigoriadis, Anastasios (Frontiers in Oral Health, 2024)
AimThe brief report aims to evaluate masticatory performance and components of chewing behavior in people with anorexia nervosa and compare it with a reference group of individuals with no history of eating disorders.Material and methodsEighteen women participated in the study: nine with anorexia nervosa (age 20.2 ± 5.9) and nine as controls in a reference group without anorexia nervosa (age 23.6 ± 0.9). Masticatory performance was assessed with a food comminution test. The participants also ate (chewed and swallowed) a second test food while their jaw movements were recorded to evaluate their chewing behavior. The number of comminuted pieces during the food comminution test, chewing cycles, chewing duration, and components like occlusal, and jaw opening/closing duration, were evaluated.ResultsIn comparison to the reference group the anorexia nervosa patients performed poorly in the food comminution test (P = 0.007), and also chewed the test food significantly longer (P = 0.004) and with significantly more chewing cycles (P = 0.014). The results also showed a significantly longer jaw-closing duration in the anorexia nervosa group compared to the reference group (P = 0.021). However, there were no significant differences in either the jaw opening or the occlusal duration between the two groups.ConclusionOverall, the results of the study indicate that the anorexia nervosa group shows signs of poor masticatory performance and altered chewing behavior compared to the reference group of individuals with no history of eating disorders.